Mapping of Rice Field to Support Food Safety at Banyumas Regency - Yugi R. Ahadiyat; Achmad Iqbal; Okti Herliana; Ahmad Fauzi; Wilis Cahyani (Politeknik Negeri Lampung., 2021)
The rice area in Banyumas Regency needs attention in an effort to support food security and avoid land conversion. The objective of this study was to update the information through mapping rice land area at Banyumas Regency based on the type of irrigation, altitude and soil type. The research method was carried out using geographic information system (GIS) -based software, then analyzed by using the overlay method and direct checking / surveying in the field. The process of analyzing spatial data of paddy fields in Banyumas Regency is mostly done by using a Geographic Information System (GIS) software tool, namely ArcView 3.2. Mapping was carried out on three variables, namely irrigation type, altitude and soil type. The results showed that the irrigated rice field type is more dominant than the rainfed type, the altitude is lowland with an altitude of 25-250 m above sea level and the dominant soil types are andosols and latosols with an area of> 12,000 ha.